Jewish Destiny in the Novels of Albert Cohen - David J. Bond (Studies in 20th & 21st Century Literature, 1976)
The unity of Cohen's novels is due to their common theme of Jewish destiny. This is traced in the lives of the Valeureux and of Solal. The Valeureux are caricatures of the Jew, and demonstrate that Jewish identity and destiny are imposed by others. Their lives are precarious because Jews are always persecuted, a message also conveyed by other persecuted characters and by Cohen's direct interventions. But the Valeureux cling to their Jewishness and exalt their religion because it teaches the need to tame man's instincts. Solal seeks success in Gentile society, but learns it is a cruel society that exploits man's instincts. He is sickened by the hypocrisy of this society, by its frivolity and by the realisation that death makes all ambition pointless. Unable to escape his Jewish background, he defends Jewish victims of Hitler, and is ostracised. He now encounters the same fate as other Jews and becomes a victim of anti-Semitism. He finally commits suicide. Neither the Valeureux nor Solal have the solution to anti-Semitism, which Cohen sees only in the State of Israel. But, while seeing Israel as the solution, Cohen is interested mainly in Jews like the Valeureux, who have preserved the Jewish identity for centuries.
Keywords: anti-Semitism; Jewish identity; Swiss literature; Albert Cohen; Solal; Mangeclous; Jewishness